RFDT learning: A pathway to elevated metacognitive and communication skills in biology education - Siswati, Bea Hana; Suratno, Suratno (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
This research aims to improve the metacognitive and communication skills of Biology Education students through the application of the Reading, Finding, Discussing & Talking (RFDT) learning model. The method used in this research is quasi-experimental with a nonequivalent control group design. The research sample consisted of 125 students divided into two groups: the experimental group which used the RFDT learning model and the control group which used conventional learning. Research instruments include metacognitive ability tests, communication ability questionnaires, as well as observations and interviews to support quantitative data. Data analysis was carried out using the t test to determine significant differences between the experimental group and the control group. The results showed that there was a significant increase in metacognitive abilities and communication skills in the experimental group compared to the control group. Students who take part in RFDT learning show an increase in their metacognitive abilities and their communication skills also increase. The application of the RFDT model also helps students understand the material more deeply through reading, finding information, discussing and speaking. This research concludes that the RFDT learning model is effective in improving the metacognitive and communication skills of biology education students. Therefore, it is recommended that this model be implemented more widely in the learning process to support the development of critical thinking and communication skills among students.